Improving production indicators through a free ERP information system - Marzall, Luciana Fighera; Santos, Lucas Almeida dos; Pentiado Gody, Leoni; Costa, Vânia Medianeira Flores (Revista de Administração da UFSM, 2018)
Inserted in a highly competitive market scenario, micro and small enterprises face numerous obstacles to remain in the market. Data surveyed reveal that 98% of Brazilian companies are micro and small, which shows their importance to the national economy. Thus, it is necessary for managers to effectively manage the work routine in order to improve the management and consequently the performance of these enterprises. Aiming to improve the management of the productive process of a small company, the present study aims to implement a free ERP management system focused on the improvement of production performance indicators. The research is classified as action research, with a qualitative and quantitative approach, having as procedure the case study. As results, indicators were verified before, during and after the implementation of the ERP system, and it was concluded through the measurement that the implemented system brought improvements to the performance of the researched organization.<pre style="text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Inserted in a highly competitive market scenario, micro and small enterprises face numerous obstacles to remain in the market. Data surveyed reveal that 98% of Brazilian companies are micro and small, which shows their importance to the national economy. Thus, it is necessary for managers to effectively manage the work routine in order to improve the management and consequently the performance of these enterprises. Aiming to improve the management of the productive process of a small company, the present study aims to implement a free ERP management system focused on the improvement of production performance indicators. The research is classified as action research, with a qualitative and quantitative approach, having as procedure the case study. As results, indicators were verified before, during and after the implementation of the ERP system, and it was concluded through the measurement that the implemented system brought improvements to the performance of the researched organization.